Principles of Child Protection in the National Criminal Code: Law Number 1 of 2023 - Dudy, Aryadi Almau; Ashady, Suheflihusnaini (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The protection of children is a state responsibility based on the principles of the Convention on the Rights of the Child (CRC). As a member state, Indonesia ratified the Convention through Presidential Decree No. 36 of 1990. This study aims to analyze the implementation of child protection principles within the National Penal Code (Law No. 1 of 2023), referencing the four main pillars of the CRC: Non-Discrimination, the Best Interests of the Child, the Right to Survival and Development, and Child Participation. In this context, the author examines the application of these principles within various provisions of the Penal Code relevant to child protection. The analysis is conducted by categorizing these provisions based on the four main pillars of the CRC. This approach seeks to assess the extent to which the Penal Code aligns with international child protection standards while identifying potential inconsistencies that could harm children as legal subjects. By categorizing these provisions, the study aims to provide a deeper understanding of the integration of CRC principles into national criminal law and their implications for child protection in Indonesia. The results indicate that these principles have been incorporated into the Penal Code through specific provisions, particularly those concerning child protection. This reflects a national commitment to safeguarding children as a vulnerable group and ensuring their rights are fulfilled in accordance with international standards.